Penerapan Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan - Rahmawati, Nur Laily; Sri Wartini; Jefri Putri Nugraha (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
This study aims to determine the application of motivation and work discipline on employee performance at PT HSS, the variables used in this study are motivation, work discipline, and employee performance. Data collection techniques used interviews, observations, documentation, and questionnaires. The sampling technique uses the Slovin formula and obtained 52 respondents. This data analysis uses multiple regression tests, validity tests, reliability tests, determination coefficients (R2), F tests, t tests. Based on the results of the test analysis, it shows that partially, work discipline has a positive and significant effect on employee performance, while work motivation does not have a significant effect. When viewed simultaneously, motivation and work discipline have a significant effect on employee performance. Therefore, companies are advised to pay more attention to employee discipline and maintain their work enthusiasm so that work results are getting better.